INCREASING OF CRITICAL THINKING STUDENTS THROUGH COOPERATIVE LEARNING MODEL TPS TYPE (THINK-PAIR-SHARE) IN SOCIAL STUDIES LEARNING (CLASSROOM ACTION RESEARCH IN CLASS VIII-1 / IBNU THUFAIL FITRAH INSANI II JUNIOR HIGH SCHOOL) - Alfian, Rian (Universitas Pendidikan Indonesia, 2017)
Abstract-This research is motivated by the problems found in the early observation in class VIII-1 / Ibnu Thufail Islamic intergrated of Junior High School Fitrah Insani II related to the critical thinking ability of learners. Lack of courage of learners in answering and asking is a low critical thinking indicator in Social studies learning. Alternative problem solving chosen is the application of cooperative learning model TPS (Think-Pair-Share) type. The problem formulation in this research is